Susceptibilidad a deslizamientos en la vía de integración barrial, desde el sector de la Argelia hasta punzara chico de la ciudad de Loja. - Rivera Miles, Mirian Mariana (2014)
This thesis work has as purpose to identify and characterize the areas prone to landslides on the road to integration neighborhood, in the stretch from Algeria until will puncture Chico of the city of Loja, Ecuador. In this project were conducted field work and office; applying engineering techniques for obtaining data in the uprisings: Topographical, geological, geomorphological, vegetative cover, in addition to the geotechnical characterization based on direct methods SPT (Standard Penetration Test) and indirect SEV (Vertical Electrical soundings); the same which will be used to correlate the water content in the strata and lithology of the sector. To obtain the final map of susceptibility to landslides was used the heuristic method in combination with the method of sum of ranges; all this with the help of Geographic Information Systems (ArcGIS 10.1), interpretation of aerial photographs, digital elevation models, resulting in the maps of the four variables with their respective weights: Geology (0.4), Geomorphology (0.3), slopes (0.2), vegetation (0.1), all this procedure was performed under the sequence of the tool "Model Builder" As a result the main objective, the susceptibility to landslides in the study area was classified into five categories: very low (10.83 %), Low (22.48 %), Medium (19.03 %), high (42.61 %) and Very High (5.05). Also conducted an inventory of landslides with the purpose of correlating with the map of susceptibility, where the majority of them are found in area of high susceptibility, each zone is related to the characterization of the practice on the basis of physical-mechanical properties and SPT of the soil. The results of this project will make it possible to shade the areas susceptible to slide so that it will be a basis for the implementation of public policies aimed at the prevention of risks in the track and its surroundings, in addition to being key elements within the project of planning and land use management.